2012
DOI: 10.1143/jjap.51.101301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radical-Doped n+ Back Surface Field Layers on the Effective Minority Carrier Lifetimes of Crystalline Silicon with Amorphous Silicon Passivation Layers Deposited by Catalytic Chemical Vapor Deposition

Abstract: To reduce surface recombination at an amorphous silicon (a-Si)/crystalline silicon (c-Si) interface in heterojunction solar cells, a thin phosphorus-doped back surface field (BSF) layer is applied to c-Si. Thin BSF layers are doped at temperatures lower than 350 °C by radical doping. The reduction in the surface recombination velocity of n-type c-Si is investigated by comparing the effective minority carrier lifetimes of c-Si samples with and without doping. Using radical-doped BSF layers, the effective minori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The BO in this study optimized the passivation quality under the i-a-Si:H deposition conditions. We have previously reported that τ eff increases with increasing i-a-Si:H thickness . Thus, we modeled τ eff as a function of the thickness in addition to the deposition condition in model 1.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BO in this study optimized the passivation quality under the i-a-Si:H deposition conditions. We have previously reported that τ eff increases with increasing i-a-Si:H thickness . Thus, we modeled τ eff as a function of the thickness in addition to the deposition condition in model 1.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We have previously reported that τ eff increases with increasing i-a-Si:H thickness. 22 Thus, we modeled τ eff as a function of the thickness in addition to the deposition condition in model 1. A BO with no constraints may converge to the conditions under which thick i-a-Si:H is deposited.…”
Section: Sample Fabricationmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] This novel doping technique, referred to as "Cat-doping", can be performed at significantly low substrate temperatures of less than 200°C, and is thus applicable to the fabrication of a-Si= c-Si heterojunction solar cells. We have already confirmed the effectiveness of P Cat-doping in reducing the SRV of minority carriers on n-type c-Si wafers.…”
Section: Introductionmentioning
confidence: 99%
“…We have already confirmed the effectiveness of P Cat-doping in reducing the SRV of minority carriers on n-type c-Si wafers. 17,18,[21][22][23] In this study, we attempt to apply P Cat-doping to actual a-Si=c-Si heterojunction solar cells. A solar cell prepared with P Catdoping shows better V oc than a cell without P Cat-doping, indicating the applicability of Cat-doping to actual solar cell devices.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that HWCVD has the advantages of conformal film deposition on small objects with high-aspect ratio structure [24,25] and no ion bombardment, which make it suitable for fabrication of devices with SiNW structure. Moreover, HWCVD technique can be used to form shallow doping layer (less than 10 nm in depth) on single-crystal silicon surface at temperatures less than 350°C by catalytically generated phosphorous radicals from hot filaments [26-29]. …”
Section: Introductionmentioning
confidence: 99%